Ketone Bodies in Neurological Diseases: Focus on Neuroprotection and Underlying Mechanisms - Yang, Huajun; Shan, Wei; Zhu, Fei; Wu, Jianping; Wang, Qun (Frontiers in Neurology, 2019)
There is growing evidence that ketone bodies—derived from fatty acid oxidation and produced during fasting or consumption of high-fat diets—can exert broad neuroprotective effects in a group of neurological diseases. Although the mechanisms underlying the neuroprotective effects of ketone bodies have not been fully elucidated, studies in recent years provided abundant evidence suggesting that ketone bodies exert neuroprotective effects through possible mechanisms including anti-oxidative stress, maintaining energy supply, modulating the activity of deacetylation and inflammatory responses. Based on the neuroprotective effects, ketogenic diet has been applicated in the treatment of neurological diseases such as refractory epilepsy, Alzheimer’s Disease, Parkinson’s Disease, and traumatic brain injury. Ketogenic diet has great potential for clinical application, which needs to be further explored. Future studies are necessary to further specify the roles of components in ketone bodies and their therapeutic target and related pathways, so as to optimal the strategy and efficacy of ketogenic diet therapy.